Development of sustainable thermoplastic jute prepregs by emulsion impregnation for biocomposites - Muhammad Mahad Umair Saqib; Asif Hafeez; Hassan Mehboob; Khubab Shaker (Composites Part C: Open Access)
The use of thermoplastic composites reinforced with plant fibers has been in high demand due to their lightweight, recyclability and sustainability. However, conventional composite manufacturing processes are incompatible with natural fibers to get the desired impregnation level with thermoplastic matrices. There is a need to develop a sustainable, economical pre-impregnation method for better resin dispersion, extended shelf life, and faster production. This study aims to investigate a method for producing thermoplastic emulsion and its processing with plant fibers. Prepregs were fabricated using jute yarn and emulsion to prepare biocomposites via compression molding. These biocomposites were fabricated with six stacking sequences (A0450, A904590, A459045, A45045, A0900, and A90090). The mechanical performance of these composites showed strong dependence on the stacking sequence. The results revealed that the highest tensile strength of 17.02 MPa was exhibited by A0450, while a reduction of 94 % and 91 % in tensile strength was observed for laminates A459045 (1.55 MPa) and A904590 (1.01 MPa), respectively. The results of the short beam test showed a similar trend with no interlaminar failure. The inherent ductile nature of the matrix resulted in a rebound during a drop-weight test, and A0450 and A90090 showed the maximum load-bearing properties. The composites produced showed proper fiber impregnation and perfect interfacial adhesion, thus overcoming the limitations associated with traditional thermoplastic matrices. Further optimization of the developed acrylic emulsion could emerge as a potential substitute for conventional thermoplastics for the development of sustainable composites.